ANALISIS YURIDIS ITIKAD TIDAK BAIK PEMOHON PAILIT TERHADAP PENYELESAIAN UTANG PIUTANG (DITINJAU DARI UU NO.37 TAHUN 2004) - Andja, Satria Braja Hari; Simamora, Pisga H; Bangun, Ricky B (JURNAL MUTIARA HUKUM, 2020)
This study aims to determine: (1) To determine the bad faith of creditors in utilizing bankruptcy as a means of collecting accounts payable. (2) To find out and analyze whether bankruptcy is a means for debtors to pay off debts. This research is a juridical-normative research which is based on literature research in order to obtain secondary data. This normative juridical research is also supported by interviews. The data obtained from legal principles, regulations and books were analyzed using qualitative methods. The results showed that (1) the Indonesian Bankruptcy Law did not anticipate the applicant's bad faith in the bankruptcy process. (2) the ease of applying for bankruptcy becomes an opening for creditors and debtors to manipulate bankruptcy. Several provisions on bankruptcy have an impact on the ineffectiveness of the provisions of this provision. Keywords: bad faith, bankruptcy